Neutralizing monoclonal antibodies against SARS-CoV-2 for COVID-19 pneumonia in a rituximab treated patient with systemic sclerosis—A case report and literature review - Yalcin Mutlu, Melek; Taubmann, Jule; Wacker, Jochen; Tascilar, Koray; Fagni, Filippo; Gerner, Maximilian; Klett, Daniel; Schett, Georg; Manger, Bernhard; Simon, David (Frontiers in Medicine, 2022)
Patients with immune-mediated diseases (IMID) such as systemic sclerosis (SSc), who are treated with B cell depleting treatments, are at risk for developing severe COVID-19 due to inadequate humoral immune response. During B cell depletion, therapeutic substitution of neutralizing monoclonal antibodies against the SARS-CoV-2 spike protein (mAbs) might be helpful to prevent severe COVID-19. It has been shown, that in non-IMID patients mABs reduce SARS-CoV-2 viral load and lower the risk of COVID-19 associated hospitalization or death. However, there are limited data on the effect of mAbs in IMID patients after exposure, especially in patients treated with B cell depleting agents. Herein, we report a case of a rituximab treated SSc patient who developed COVID-19 and was successfully treated with a combination of mAbs (casirivimab/imdevimab). With this case we show that IMID patients may benefit from post-exposure administration of mAbs. In our case treatment with neutralizing autoantibodies was safe and a possible contributor in protecting the patient from mechanical ventilation and eventually death. We frame this case within the current evidence from the literature and provide a perspective on the future potential role of mAbs for treating IMID patients suffering from COVID-19.